Incremental Validity of the Frame-of-Reference Effect in Personality Scale Scores: A Replication and Extension. - Bing, Mark N.; Whanger, James C.; Davison, H. Kristl; VanHook, Jayson B. (Journal of Applied Psychology, 2004)
Context-specific personality items provide respondents with a common frame of reference unlike more traditional, noncontextual personality items. The common frame of reference standardizes item interpretation and has been shown to reduce measurement error while increasing validity in comparison to noncontextual items (M. J. Schmit, A. M. Ryan. S. L. Stierwalt. & S. L. Powell, 1995). Although the frame-of-reference effect on personality scales scores has been well investigated (e.g., M. J. Schmit et al., 1995), the ability of this innovation to obtain incremental validity above and beyond the well-established, noncontextual personality scale scores has yet to be examined. The current study replicates and extends work by M. J. Schmit et al. (1995) to determine the incremental validity of the frame-of-reference effect. The results indicate that context-specific personality items do indeed obtain incremental validity above and beyond both noncontextual items and cognitive ability, and in spite of socially desirable responding induced by applicant instructions. The implications of these findings for personnel selection are discussed.